2020 Renewal planning for Lagankhel Center urban public space analysis and recommendation - Bista, Sanchita (Quezon City College of Architecture, University of the Philippines Diliman, 2003)
Many city centers in Nepal are already in the state of blight, especially when urbanization is still new in the country. Among the 58 urban centers in Nepal, 20 are already loosing their population. Old historic cities are concentrated with more preservation focus, but the newer centers seem neglected and allowed to spread in its own terms. The gulf between affluent newer suburbs and declining central cities are starting to become a growing phenomenon. This thesis seeks to understand the prospects for more successfully addressing some of the persistent urban problems in one of the most pressured centers in Nepal, Lagankhel located in Lalitpur City of Kathmandu Valley. Using access and linkages, activities, image and sociability as the four main criteria for the basis of this particular urban public space analysis, this thesis attempts to propose a 2020 renewal planning vision for the selected study center. Under each of the research factor, the efficiency of Lagankhel Center is analyzed to realize its potentials and weakness. Being at the edge of the Lalitpur City Protected Monument under the World Heritage Sites, Lagankhel Center projects its own specific culture and religious importance, which has to be considered in the direction of the Renewal Masterplan for the whole area itself.
Thesis (Master of Architecture: Community Architecture)--University of the Philippines, Diliman
Keywords: Lagankhel Center -- Kathmandu Valley (Nepal).; Urban renewal -- Kathmandu Valley (Nepal)